Pengaruh Kualitas Pelayanan Akademik Terhadap Kepuasan Mahasiswa di Politeknik Negeri Batam - Lidya Mariska; Shinta Wahyu Hati (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2015)
This study is expected to determine the influence of the dimensions of quality of service which include reliability, responsiveness, assurance, empathy, and tangible to Batam Polytechnic student satisfaction. The method used in this research is quantitative approach with explanatory research. Data analysis technique employs multiple linear analysis. Population in this research is the students of Multimedia and Networking Techniques who started their academic year in 2014, 2013, 2012 at Batam Polytechnic. The sample used in this study was 100 respondents. The sampling technique is purposive sampling.The results of this study show that hypothesis 1 variable reliability, hypothesis 2 responsivenss variable, hypothesis 3 variables assurance, empathy hypothesis 4 variable, hypothesis 5 tangible variable, indicate signifant value which is smaller than α = 0.05 and is proven by F - calculate> F - table. The results show that Ho is refuted and Ha is supported. It can be said that partial variable quality of service that include reliability, responsiveness, assurance, empathy, and tangible has a positive and significant impact on student satisfaction. Simultaneous test results that have been done show that empathy and tangible variables have a dominant influence on student satisfaction.